2018
DOI: 10.1089/ten.tea.2017.0299
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mechanics of a Pectin-Based Pleural Sealant after Lung Injury

Abstract: Pleural injury and associated air leaks are a major influence on patient morbidity and healthcare costs after lung surgery. Pectin, a plant-derived heteropolysaccharide, has recently demonstrated potential as an adhesive binding to the glycocalyx of visceral mesothelium. Since bioadhesion is a process likely involving the interpenetration of the pectin-based polymer with the glycocalyx, we predicted that the pectin-based polymer may also be an effective sealant for pleural injury. To explore the potential role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…In previous work, we showed that structural heteropolysaccharides function as pleural sealants in mice. 10 The similarity between the human and murine glycocalyx suggested the possibility of a comparable sealant function in humans. Here, we show the efficacy of structural heteropolysaccharides in sealing human pleura.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, we showed that structural heteropolysaccharides function as pleural sealants in mice. 10 The similarity between the human and murine glycocalyx suggested the possibility of a comparable sealant function in humans. Here, we show the efficacy of structural heteropolysaccharides in sealing human pleura.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse studies have demonstrated an effectively sealed pleural injury, with no pleural adhesions or evidence of toxicity, when studied over 7 days. 10 Finally, the presence of pectin-based mixtures in human food and oral medication capsules [30][31][32] suggests that the pectin-based sealant will be similarly nontoxic in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, pectin interpenetrates the PAA networks and strengthens the hydrogel. Second, pectin contains a large number of -OH and -COOH groups, which are important active sites of hydrogen bonds in the noncovalent interaction with acrylic acid and quercetin ( Servais et al., 2008 ). Thus, quercetin, PAA, and pectin form noncovalent interactions, which dissipate energy under large deformation and improve the mechanical properties of the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…The practical implications of these phase transitions are relevant to biomedical applications. For example, the ability to recover from large elastic strains during deformation is a crucial feature of pectin's functional utility as a mesothelial sealant (Servais, Valenzuela, Kienzle, et al, ). The mesothelium, the surface layer of internal organs, is associated with extraordinary stresses during normal organ function; these stresses include the movement associated with the beating heart, ventilating lung, and peristaltic bowel.…”
Section: Discussionmentioning
confidence: 99%